iPS cells generation: an overview of techniques and methods - Telpalo-Carpio SA (Journal of Stem Cells and Regenerative Medicine, 2013)
Cell therapy is one of the principal and most promising research areas of regenerative medicine. Nevertheless different ethical problems related with the use of embryonic stem cells arise from this technology. Thus the search for a feasible way of stem cells generation is in current investigation. Induced pluripotent stem (iPS) cell is one of the most encouraging emerging technologies that represent a solution to this problem. Different methods that change cell protein and gene profiles, as well as its morphology and function, driving the cell to the stem cell state have been developed. These include nuclear transfer, the usage of cell extracts and synthetic molecules, the forced expression of defined genes and cytoplasmatic level modifications. Even though favorable results have been achieved, there are still issues that require special attention. Advances with non-integration methods are now available but dedifferentiation efficiency is yet an area of opportunity. The main objective of this review is to show the most important techniques, their advantages and opportunity areas in the field of iPS cell generation.